Was there a Sword? On Aristophanes’ Thesmophoriazusae (v. 134–140) - Sergey A. Stepantsov (Studia Litterarum)
In the prologue of Aristophanes’ Thesmophoriazusae (134–140) Euripides’ Inlaw after seeing the poet Agathon expresses his bewilderment at the mixture of gender signals emitted by Agathon’s clothes and the objects he is surrounded with. Inlaw enumerates several couples of objects incompatible because of their relatedness to one or another gender: barbitos and saffron gown, lyre and headband, lekythos (an attribute of athletics) and breast band, sword and mirror. In this paper I reconsider commentators’ opinions on the question whether there was indeed a sword among the props visible to the public or the sword was mentioned by Inlaw because it was present in the passage from Aeschylus’ Edonians explicitly parodied in the questions asked by Inlaw. A. Sommestein’s speculation that Agathon needs a sword to get into a male role is rejected as contradicting Agathon’s words in v. 154–155. I also call in question G. Kaibel’s surmise (supported by C. Prato, C. Austin and D. Olson) that the sword was present in the parodied scene of the Edonians because Dionysus was represented in armis there, as a conqueror of new lands. I consider that there are no firm reasons to think that there was a sword among the props of the comedy or that it was mentioned in the parodied tragedy as a thing present in the scene in which Lycurgus interrogated Dionysus. It is more probable that sword (as well as lekythos) is mentioned by Inlaw just as a most typical male thing opposed to typically female mirror. I also suppose that v. 140 “What can a sword and a mirror have in common?” is rather a recast of the anonymous comic aphorism “What can a blind man and a mirror have in common?” (apud Stob. 4.30.6a) than vice versa (whoever the author of this aphorism might be).